Modulation of Ultrafast Conformational Dynamics in Allosteric Interaction of Gal Repressor Protein with Different Operator DNA Sequences. (3rd March 2016) - Choudhury, Susobhan; Naiya, Gitashri; Singh, Priya; Lemmens, Peter; Roy, Siddhartha; Pal, Samir Kumar
Abstract: Although all forms of dynamical behaviour of a protein under allosteric interaction with effectors are predicted, little evidence of ultrafast dynamics in the interaction has been reported. Here, we demonstrate the efficacy of a combined approach involving picosecond‐resolved FRET and polarisation‐gated fluorescence for the exploration of ultrafast dynamics in the allosteric interaction of the Gal repressor (GalR) protein dimer with DNA operator sequences OE and OI . FRET from the single tryptophan residue to a covalently attached probe IAEDANS at a cysteine residue in the C‐terminal domain of GalR shows structural perturbation and conformational dynamics during allosteric interaction. Polarisation‐gated fluorescence spectroscopy of IAEDANS and another probe (FITC) covalently attached to the operator directly revealed the essential dynamics for cooperativity in the protein–protein interaction. The ultrafast resonance energy transfer from IAEDANS in the protein to FITC also revealed different dynamic flexibility in the allosteric interaction. An attempt was made to correlate the dynamic changes in the protein dimers with OE and OI with the consequent protein–protein interaction (tetramerisation) to form a DNA loop encompassing the promoter segment. Abstract : Complex operations : We investigated DNA operators (OE /OI ) bound to a dimer of Gal repressor while undergoing allostery‐driven tetramerisation. OE operator DNA induces more domain fluctuation in the protein compared to OI . But flexibility around IAEDANS was more evident for the OI –protein complex than that for the OE complex.